2023
DOI: 10.1002/adfm.202302989
|View full text |Cite
|
Sign up to set email alerts
|

Layer Sliding And Twisting Induced Electronic Transitions In Correlated Magnetic 1t‐Nbse2 Bilayers

Abstract: Correlated 2D layers, like 1T‐phases of TaS2, TaSe2, and NbSe2, exhibit rich tunability through varying interlayer couplings, which promotes the understanding of electron correlation in the 2D limit. However, the coupling mechanism is, so far, poorly understood and is tentatively ascribed to interactions among the orbitals of Ta or Nb atoms. Here, it is theoretically shown that the interlayer hybridization and localization strength of interfacial Se pz orbitals, rather than Nb orbitals, govern the variation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Therefore, it is reasonable to consider CrInS 2 as a mixed Mott insulator and charge transfer (CT) insulator. 65,66 Through detailed investigation of the PDOS and band structures across the entire CrInX 2 system, it has been found that the bonding states progressively shift to higher energy levels due to the gradual decrease in Table 1 The lattice constant (a 0 ), Cr-X 1 bond length (l 1 ), Cr-X 2 bond length (l 2 ), Cr-X 1 -Cr bond angle (y 1 ), and Cr-X 2 -Cr bond angle (y 2 ) of the CrInX 2 monolayer at the GGA+U level. The band gaps (E g ) at the GGA+U and HSE06 levels electronegativity along the S -Se -Te series, while the antibonding states move to lower energy levels and cross the E F in the spin-down channels, consequently imparting metallic characteristics to CrInTe 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is reasonable to consider CrInS 2 as a mixed Mott insulator and charge transfer (CT) insulator. 65,66 Through detailed investigation of the PDOS and band structures across the entire CrInX 2 system, it has been found that the bonding states progressively shift to higher energy levels due to the gradual decrease in Table 1 The lattice constant (a 0 ), Cr-X 1 bond length (l 1 ), Cr-X 2 bond length (l 2 ), Cr-X 1 -Cr bond angle (y 1 ), and Cr-X 2 -Cr bond angle (y 2 ) of the CrInX 2 monolayer at the GGA+U level. The band gaps (E g ) at the GGA+U and HSE06 levels electronegativity along the S -Se -Te series, while the antibonding states move to lower energy levels and cross the E F in the spin-down channels, consequently imparting metallic characteristics to CrInTe 2 .…”
Section: Resultsmentioning
confidence: 99%